Inner city and Stationary Retail—an Inseparable Couple? What are the Implications of Online Trading? - Stepper, Martina (Raumforschung und Raumordnung | Spatial Research and Planning, 2016)
Stationary retail and inner cities have a tight interconnection on the spatial level. Due to the increasing importance of Internet and online trading in everyday life, however, the physical space as a constant link currently becomes less important. Against the background of general lack of time and the benefits, which online trading provides, more and more products are purchased online. This is also reflected in the trading volume. While counter retail has made almost stagnant sales in recent years, the growth rates in online commerce are immense. The online share of total retail sales is expected to grow to around 15 % by 2025. This is not without consequences for urban retail locations. There will be—depending on their localization in cities that are favored or disadvantaged in spatial-structural terms—both winners and losers. To keep the impact on affected areas as low as possible, the opportunities offered by the increasing digitization should be used as an opportunity for increasing the attractiveness of inner-city retail locations.
Keywords: Inner city; Stationary retail; Online trading; Inner-city retail locations